Evaluation of knowledge of dental practitioners in Isfahan of pharmacological methods of anxiety control - Naser Kaviani; Bahzad Bagheri; Elham Sadat Benandeh (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Based on data available, about 10% of people have severe dental anxiety. There are several methods to control dental anxiety, the use of which entails knowledge on behalf of the dental practitioners and appropriate equipment. This study evaluated knowledge of dental practitioners about dental anxiety control methods.Materials and Methods: In this study descriptive study, 249 dental practitioners in Isfahan were selected using simple sampling method and given a questionnaire consisting of 20 questions about pharmacological methods to control dental anxiety in patients. Data was analyzed with SPSS software using ANOVA at a significance level of 0.95. Knowledge scores were reported from 0 to 20.Results: Knowledge scores for inhalation sedation, oral sedation and general anesthesia were 12.65 ± 3.31, 13 ± 2.84, and 17.91 ± 6.12, respectively. Mean of dental knowledge scores of dentists in relation to pharmacological sedation techniques was above 12, indicating proper knowledge level of dental practitioners. ANOVA did not reveal any significant differences in knowledge level means between different age groups in relation to general anesthesia (p value = 0.217). However, there were significant differences in the knowledge means between various age groups in relation to inhalation (p value = 0.036) and oral sedation (p value = 0.035) techniques. Conclusion: Under the limitations of this study the knowledge of dentists about pharmacological methods of controlling patient anxiety in dentistry was good but these methods are not widely used due to lack of background support. Given the importance of such measures, it is necessary to increase the knowledge of the community about these techniques. Key words: Anesthesia, Conscious sedation, Dental anxiety, Knowledge.